The Effect of Extensive Reading on Vocabulary Knowledge of First Level University Students - Carolina, Campana Dias Diana; Yadira, Cardenas Moyano Maria; Oswaldo, Guadalupe Bravo Luis; Antonio, Bravo Montenegro Marco; Antonio, Urena Lara David (European Scientific Journal, ESJ, 2019)
The objective of the research was to analyze how extensive reading or reading for pleasure can improve the development of vocabulary in a sample of 48 first-level university students of the Universidad Tecnológica Indoamérica in the city of Ambato. It was an experimental, bibliographic, descriptive, field and correlational research. To determine the correlation between the two study variables, a deep and thorough investigative analysis of books, journals and research was carried out. An intervention plan was applied through the use of a handbook of 19 vocabulary activities and to measure the knowledge of the vocabulary in the students, an observation card was used in order to measure attitudes and behavior towards extensive reading. A questionnaire of twelve questions related to word knowledge and the word form with its meaning was used as well. The research contains the sociodemographic statistical analysis of the participants and an analysis of the results of the evaluation of reading knowledge and vocabulary to know the descriptive aspects. Furthermore, the descriptive analysis of the vocabulary knowledge assessment from a global point of view and the aspects of word knowledge was carried out; to finally perform the analysis of the presence and degree of correlation between extensive reading and vocabulary knowledge, using the Pearson coefficient. Thus, it allowed to determine that, the existence of the correlation between the two variables investigated. That is to say, the results indicated that the use of extensive reading influences the development of students’ vocabulary by raising interest and improving vocabulary.